Differences in warming impacts on wheat productivity among varieties released in different eras in North China. (5th May 2015) - ZHENG, C. Y.; CHEN, J.; SONG, Z. W.; DENG, A. X.; JIANG, L. N.; ZHANG, B. M.; ZHANG, W. J.
SUMMARY: Ten leading varieties of winter wheat released during 1950–2009 in North China were tested in a free-air temperature increase (FATI) facility. The FATI facility mimicked the local air temperature pattern well, with an increase of 1·1 °C in the daily mean temperature. For all the tested varieties, warming caused a significant reduction in the total length of wheat growth period by 5 days and especially in the pre-anthesis period, where it was reduced by 9 days. However, warming increased wheat biomass production and grain yield by 8·4 and 11·4%, respectively, on an average of all the tested varieties. There was no significant difference in the warming-led reduction in the entire growth period among the tested varieties. Interestingly, the warming-led increments in biomass production and grain yield increased along with the variety release year. Significantly higher warming-led increases in post-anthesis biomass production and 1000-grain weight were found in the new varieties compared to the old ones. Meanwhile, a significant improvement in plant productivity was noted due to wheat breeding during the past six decades, while no significant difference in the length of entire growth period was found among the varieties released in different eras. The results demonstrate that historical wheat breeding might have enhanced winter wheat productivity and adaptability through exploiting the positive effects rather than mitigating the negative impacts of warming on wheat growth in North China.